1997
DOI: 10.1046/j.1365-2842.1997.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of endodontic posts

Abstract: Twenty-two commercially available endodontic posts were examined with regard to stiffness, elastic limit and resistance to fracture. Differences in mechanical properties were explained by differences in width, shape and surface structure. In the selection of an endodontic post, its stability rather than its retention should be of primary clinical concern. Accordingly, the authors advocate the use of endodontic posts that have a cylindrical coronal portion and a conical apical portion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 4 publications
2
26
0
2
Order By: Relevance
“…Burns et al (79) reported minimal effects of the post length on stress distribution within dentine. Other studies supported this finding and found no effect of the post length on fracture resistance of restored teeth (45,80,81). Giovani et al (82) found no effect of post length on the fracture resistance of teeth restored with metal cast post and core.…”
Section: Post Lengthmentioning
confidence: 88%
“…Burns et al (79) reported minimal effects of the post length on stress distribution within dentine. Other studies supported this finding and found no effect of the post length on fracture resistance of restored teeth (45,80,81). Giovani et al (82) found no effect of post length on the fracture resistance of teeth restored with metal cast post and core.…”
Section: Post Lengthmentioning
confidence: 88%
“…2 These posts are used when there is an insufficient volume of natural dentine to restore the dental crown to its natural shape, shade and function with a fixed prosthetic appliance or restoration, called a prosthetic crown. 3,4 Recently, a novel RDP with a so-called retentive core was designed. 5 This core can be adjusted to a suitable form for each individual case by adding suitably translucent porcelain, or it can be easily reshaped by grinding with dental burs.…”
Section: Introductionmentioning
confidence: 99%
“…The static or dynamic behavior of resin-fiber posts depends on the composition (fiber type and density) as well as the fabrication process and, in particular, the quality of the resin-fiber interface. In an in vitro study examining physical properties of various posts, it was concluded that the ideal post design comprises a cylindrical coronal portion and a conical apical portion [23]. Much discussed is still the ideal post length, if one part provides greater stability to prosthetic rehabilitation at the same time involves removal of dentin [24] and more because of the existing limitations of adhesive procedures within the root canal [25–27].…”
Section: Discussionmentioning
confidence: 99%